Heterogeneous Agglomeration Economies in the Developing Countries : The Roles of Firm Characteristics, Sector Tradability, and Urban Mobility - Burger, Martijn; Ianchovichina, Elena; Akbar, Prottoy Aman (Washington, DC: World Bank, 2022)
Using geo-coded, firm-level data on more than 51,000 establishments in 649 metropolitan areas in 98 developing economies, from the World Bank’s Enterprise Surveys and a new global database on city-level mobility and congestion, this paper estimates the “pure” firm productivity gains of urban density, net of negative externalities associated with limited mobility, crime, and pollution. The results suggest that the average size of agglomeration economies in the developing world is comparable to the one observed in advanced countries, but the magnitude of the benefits of density on firm productivity substantially varies across firms. Returns to urban density are higher for firms operating in the tradables sector, exporters, foreign-owned firms, larger firms, and more experienced firms. Agglomeration economies are lost through both limited uncongested mobility and congestion, but the latter has a stronger negative effect on agglomeration economies and reduces relatively more the agglomeration benefits of firms in the non-tradables sector than those producing tradables.